PEMANFAATAN APLIKASI GOOGLE SEBAGAI PENUNJANG ADMINISTRASI PADA PAUD INSAN MULIA DUA - Norhikmah (Politeknik Negeri Sriwijaya, 2022)
Since 2020 the covid pandemic has hit Indonesia, one of the sectors affected is the education sector, one of the impacts experienced is that some school administration is carried out online, thus indirectly demanding early childhood education institutions to upgrade the knowledge of their teachers to be literate in information technology, especially online applications such as Google, such as Google Drive, Google Doc and Google Excel, so far, Paud Insan Mulia has two separate storages, not in one place, for example on each teacher's computer or laptop, so that if needed, they are immediately copied using Flash or sent via a group. WA, and if there is a change in the file, the other teachers cannot know in real time, the making of school activity reports is done individually using MS Word, so if there are teachers in charge of the same class, they cannot do or make together at one time and and sa The file, recording of tuition payments and overtime pickup are recorded using a book, and manually recapitulated. And the creation and distribution is done manually, therefore to overcome the above problems, offline training or workshops are needed with the use of using the Google application as a support in file management.